Ecology of Persian Walnut (Juglans regia L.) in Western Bhutan - Sagar, Laxmi; Jambay; Gyeltshen, Ngawang; Ghalley, Bhakta Bdr; Yonten, Sonam; Gyeltshen, Namkha; Subedi, Rupesh; Dorji, Rinchen (International Journal of Environment, 2022)
In Bhutan the Persian Walnut (Juglans regia L.) is highly valued for its timber and is listed under special class in Royalty on Forest Products of Bhutan. Possessing high timber and other medicinal values, the ecology of the species in the country was poorly understood. The study aimed to understand the ecological requirements and habitat modeling of the species in Bhutan. A purposive non-probability sampling was adopted in natural habitats of the species in four districts (Gasa, Punakha, Wangdue Phodrang, and Dagana) of the country. Plot size of 20 m X 20 m (major plot) for tree and understory and 2 m X 2 m for ground cover were used to collect vegetation data. Soil samples were collected from the center of the major plot at a depth of 25 - 30 cm. A total of 163 plant species belonging to 74 families were recorded from the study plots. Pearson and Kendal correlation of CCA Ordination showed moderate influence of slope (r = .66) followed by altitude (r =.55). Annual mean temperature and rainfall showed moderately negative correlation with the growth and distribution of J. regia (r =. -54 and -.64) in the study area. Despite, scattered distribution of J. regia in the country an area of 7146.53 km2 which accounts for 18.61% of the country’s total area was found to be suitable for the growth and development of the species which can be used for protection and management of species in future.